Writing Assessment by The Seventh-Grade English Teacher in SMPI Al-Abidin of Surakarta - Nabilah, Farah Putri; Budiharso, Teguh; 'Arifin, Zainal; Al Fatah, Muhammad Husin (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
This study aims to investigate the writing assessment techniques employed by seventh-grade English teachers at SMPI Al-Abidin of Surakarta and evaluate how these assessments reflect students' writing abilities. Using a qualitative approach with content analysis, data were gathered from teacher interviews and document analysis of student work. This research adopts the theoretical frameworks of Zhang and Wildemuth, combined with Braun and Clarke's thematic analysis, to systematically examine the teacher's assessment methods and effectiveness. The findings reveal that the teacher predominantly utilizes the Cambridge International mark scheme for writing assessments, ensuring consistent evaluation based on content, organization, language, and communicative achievement criteria. Results show that students generally meet satisfactory performance levels across these criteria, demonstrating proficiency in content clarity, grammatical structure, and coherence. This study contributes to the broader understanding of effective writing assessment practices in secondary education, highlighting the alignment between international assessment standards and local teaching practices to support students' writing development.